PENGARUH MODEL PEMBELAJARAN TALKING STICK DISERTAI HANDOUT TERHANDAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP NEGERI 25 MUKOMUKO - Sinarni, Sinarni; Sudirman, Sudirman; Maizeli, Annika (Pendidikan Biologi, 2014)
Â ABSTRACTÂ This research was conducted due to the studentsâ low Â learning achievement in Biology in class VIII of SMP Negeri 25 Mukomuko . This problem was derived from the student who got discouraged and passive in learning, and the unavailability of textbooks. One of the efforts done to solve this problem was by applying talking stick learning model assisted with handout. The aim of this research was to reveal the effect of using talking stick learning model assisted with handout on the studentsâ learning achievement in Biology in class VIII of SMP Negeri 25 Mukomuko in academic year 2013/2014. This was an experimental research which applied Randomized Control Group Posttest Only Design. The population of the research was the students in class VIIIa was chosen as the experimental class, and class VIIIb was taken as the control class. The instrument of the research was a posttest in the from of multiple choice test containing 30 intems. The data collected was analyzed by using t-test. Based on the result of data analysis, it was found that the studentsâ average score in the experimental class was 73,92 in which the standard deviation value was 12,61, and the studentsâ average score in the control class was 59,78 in which the standard devation value was 14,19. The result of the t-test indicated that the value of tcalculatedÂ  (3,29) was bigger than ttableÂ  (1,68). Based on these results, it was calculated that the use of Talking Stick learning Â model Â assisted Â with Â Handout Â could Â improve Â the Â studentsâ Â learningÂ  achievement in biology in class VIII of SMP Negeri 25 Mukomuko